Кам’яні іконки: образ і функція. Візантійська традиція в давній Русі - Архипова, Є. (Студії мистецтвознавчі, 2007)
The tradition of manufacturing and wearing of stone icons with relief images of saints has come to Rus from Byzantium and later become an integral part of its spiritual and art culture. Proceeding from the form and subjects the destination of a carved icons was traditionally connected with the personal godliness of believers. Among the subjects of the Byzantine sanctity found on the territory of Ancient Rus the small icons and cameos prevail. The constant pray about protection determines one of the main functions of the icons-pendants with images of holy patrons of owners in the believer’s life. The icons with the depiction of Great Feasts and especially revered saints, that usually reproduced on an objects of “Pilgrim Art”, probably, could come to Rus with a pilgrims and be a some kind of eulogia or “relics-copies”.